OUTCOME OF EMBOLECTOMY IN PATIENTS PRESENTING LATE WITH ACUTE LIMB ISCHEMIA - Siddique, Afzal; Imtiaz, Nauman; Pervaiz, Khalid; Ali, Kishwar; Ahmad, Rai; Haider, Fazal-e (Journal of Ayub Medical College Abbottabad, 2020)
Background: The aim of this study is to share our experience regarding outcome of embolectomy in the patients presenting late with acute limb ischemia. It was a cross sectional descriptive study, conducted at CMH Rawalpindi from January 2016 to December 2017. Methods: All those patients having non-traumatic acute limb ischemia presenting between 6 to 72 hours of the onset of symptoms with viable affected limb were included. Their data was analysed for demography, involved limb, time of embolectomy, fasciotomy, re embolectomy, amputations, reperfusion injuries and death. The patients presenting later than 72 hours, irreversible Ischemia and limb ischemia secondary to trauma or graft occlusion of previous Bypass surgery were excluded from the study. Results: A total of 49 (36 males and 13 females) patients were included in the study. Thirty-three (67.3%) patients underwent embolectomy for lower while 16 (32.6%) for upper limb ischemia. Ten (20.4%) patients had fasciotomy while 7 (14.2%) patients underwent re embolectomy. In 5 (10.2%) patients vascular bypass had to be done. Seven (14.2%) patients underwent minor amputations while 5 (10.2%) had major limb amputations. Two (4%) patients died of reperfusion injury. Overall 42 (85.7%) limbs were salvaged. Conclusion: Embolectomy is effective in late presenting acute limb ischemia with viable extremity and should be offered to these patients. Keywords: Acute Limb Ischemia; Fasciotomy; Embolectomy